Kurikulum dan Evaluasi dalam Pendidikan Inklusi (Manajemen Sekolah) di SDN Pondok Bahar 03 - Nurfadhillah, Septy; Wahyuni, Ayu; Hartana, Davina Dewi; Azhari, Nurfidia (ALSYS, 2022)
Inclusive education is an ideology, system and or educational strategy where all children from various conditions can attend education in an educational environment together, with an educational service system that is tailored to the needs of each child. This study aims to describe the curriculum and evaluation in inclusive education in elementary schools. This type of research is qualitative research. Through the use of data collection techniques of observation, interviews and documentation. The samples of this study were special assistant teachers (GPK) and students with special needs at SDN Pondok Bahar 03. The results of this study were . The process of implementing inclusive education at SDN Pondok Bahar 03 is in accordance with the indicators of success in implementing inclusive education. The curriculum used at SDN Pondok Bahar 03 uses the inclusive curriculum and the K 13 curriculum in the learning process in the regular class. The evaluation in inclusive education at SDN Pondok Bahar 03 is carried out like evaluations in regular schools, such as daily tests, Mid-Semester Assessments (PTS) and Final Semester Assessments (PAS). The evaluation that runs at SDN Pondok Bahar 03 is appropriate because if there is a program that is not suitable, it will add a program or plan a reprogram all depending on mutual agreement